Evidence for multiple paternity and confirmation of an Indo-Pacific origin of blacktip shark Carcharhinus limbatus occurring in South Africa. Issue 3 (7th October 2019) - Bester-van der Merwe, AE; Maduna, SN; Hull, KL; Bell, J; Rossouw, C; Wintner, SP
Abstract : The blacktip shark Carcharhinus limbatus is a cosmopolitan species found in warm-temperate, subtropical and tropical waters around the world. The research here aimed to assess whether multiple paternity exists in South African C. limbatus and to confirm phylogeographic patterns previously observed within the species. A minimum and maximum frequency of 50% and 71% multiple paternity, respectively, were observed in 14 litters genotyped with five microsatellite markers. Based on the mitochondrial control region, relatively high nucleotide and haplotype diversity characterised the South African sampling population, and pairwise φST values indicated that it significantly differed from the populations of the Pacific and the western Atlantic oceans. The haplotype network showed that the South African samples were grouped closely with the Australian, Indo-Pacific and West African C. limbatus samples, which is suggestive of an Indo-Pacific origin for this population. This study is the first to report multiple paternity in this species. Furthermore, the results reveal that C. limbatus from South Africa is genetically diverse and phylogeographically distinct from most other C. limbatus populations.